Experimental studies on the development of Contracaecum rudolphii (Nematoda: Anisakidae) in copepod and fish paratenic hosts - Moravec, František (Folia parasitologica, 2009)
The larval development of the nematode Contracaecum rudolphii (Rudolphi, 1819), a common parasite of the proventriculus of cormorants, was experimentally studied. Within the eggs cultivated in freshwater under laboratory temperatures of 20–22 °C, the developing larva undergoes two moults on days 4–5, attaining the third larval stage. Most of the ensheathed third-stage larvae, 291–457 µm long, hatch spontaneously from egg shells on days 5–6. Experiments have indicated that hatched ensheated third-stage larvae and those still inside egg capsules are already infective to copepods and fishes, which both can be considered paratenic (metaparatenic) hosts. Five copepod species, Acanthocyclops vernalis, Cyclops strenuus, Ectocyclops phaleratus, Eucyclops serrulatus and Megacyclops viridis, the isopod Asellus aquaticus and small carps Cyprinus carpio were infected by feeding them these larvae. In addition, 9 fish species, Alburnoides bipunctatus, Anguilla anguilla, Barbatula barbatula, Cyprinus carpio, Gobio gobio, Perca fluviatilis, Phoxinus phoxinus, Poecilia reticulata and Tinca tinca, were successfully infected by feeding them copepods previously infected with C. rudolphii third-stage larvae. In fishes, larvae from copepods penetrate through the intestinal wall to the body cavity, where, in a few weeks, they become encapsulated; the larvae substantially grow in fish, attaining the body length up to 4.87 mm. In carp fry, the nematode third-stage larvae survived for about 15 months (up to 18 months in fish infected directly, i.e., without copepods). One small cormorant (Phalacrocorax carbo sinensis) was successfully infected by feeding it with copepods harbouring C. rudolphii third-stage larvae.
Keywords: Bird Diseases; Animals; Financing, Organized; Charadriiformes; Nematoda; ryby; financování organizované; Fishes; nemoci ptáků; hlístice; zvířata; Copepoda